2003
DOI: 10.1186/1471-2164-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet to predict bacterial ori and ter: a tendency towards a physical balance

Abstract: Background: Chromosomal DNA replication in bacteria starts at the origin (ori) and the two replicores propagate in opposite directions up to the terminus (ter) region. We hypothesize that the two replicores need to reach ter at the same time to maintain a physical balance; DNA insertion would disrupt such a balance, requiring chromosomal rearrangements to restore the balance. To test this hypothesis, we needed to demonstrate that ori and ter are in a physical balance in bacterial chromosomes. Using wavelet ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Finally, ori and ter of E. coli were predicted using GC skew, keto and purine excesses, low‐pass filtering by FFT, and elimination of subgenomic regions. The predicted results were compared with experimentally confirmed loci [35] and with the prediction by Song et al [19], which has the best accuracy among methods that utilize compositional information with wavelet transform (Table 1 ). Elimination of statistically high/low GC regions, intergenic regions, predicted HGT regions, and genes documented in HGT‐DB, used as a control in comparison with noise reduction by FFT, had either very little (for ter ) or no (for ori ) effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, ori and ter of E. coli were predicted using GC skew, keto and purine excesses, low‐pass filtering by FFT, and elimination of subgenomic regions. The predicted results were compared with experimentally confirmed loci [35] and with the prediction by Song et al [19], which has the best accuracy among methods that utilize compositional information with wavelet transform (Table 1 ). Elimination of statistically high/low GC regions, intergenic regions, predicted HGT regions, and genes documented in HGT‐DB, used as a control in comparison with noise reduction by FFT, had either very little (for ter ) or no (for ori ) effect.…”
Section: Resultsmentioning
confidence: 99%
“…Compositional skews may be disrupted by genomic insertions and by lateral gene‐transfer events [19]. To take into account the effects of these events as the control for comparison of noise reduction by FFT, we also predicted ori and ter after masking four types of subgenomic regions, namely, (1) intergenic regions; (2) low/high GC regions; (3) predicted regions of horizontal gene transfer (HGT) based on codon usage; and (4) horizontally transferred genes listed in the horizontal gene transfer database (HGT‐DB) [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have explored the reasons why some bacteria undergo frequent recombination events but many of their close relatives do not, such as in the case of serovar Typhi versus serovar Typhimurium (26,28,30). Previously, it was demonstrated that bacterial genomes have a tendency to obtain a physical balance (44). Based on this and other evidence, it was hypothesized that recombination may help the bacteria to rebalance the genome following major genomic insertions or deletions, which may have disrupted the genomic balance (19,30,31), although this hypothesis needs to be tested further as exceptions awaiting explanation also exist.…”
Section: Discussionmentioning
confidence: 99%
“…All currently available computational methods for the identification of oriC sequences in bacterial chromosomes rely on nucleotide disparities on the leading and lagging strand of the DNA double helix (13)(14)(15)(16)(17). As replication usually extends from oriC bidirectionally, it is one of two chromosomal sites where the leading and lagging strand switch places.…”
Section: Introductionmentioning
confidence: 99%